Evolution in swimming science research: content analysis of the "Biomechanics and Medicine in Swimming" Proceeding books from 1971 to 2006 - Barbosa, Tiago M. (2011)
The aim of this study was to analyze the evolution of the swimming science research based on the content analysis of the “Biomechanics and Medicine in Swimming” Proceedings books from 1971 to 2006